Faktor, povyšajušcij verojatnost' travm u borcov vol'nogo stilja - Chechelnitskaya, S. M.; Arustamian, G. V.; Vorobiev, A. V. (Vestnik Moskovskogo gorodskogo pedagogiceskogo universiteta. Serija «Estestvennye nauki», 2014)
The article is devoted to the study of the regularities of traumatisation of freestyle wrestlers. On the basis of expert Delphi method the authors determined the main causes of injury in this sport and their weights. On the basis of factor analysis three groups of interrelated reasons were singled out: injuries in a situation of training, injuries in a situation of competition and psychophysiological state of the athlete. It was proved that the violation of art movement that is recognized by all experts as the main cause of injury depends on a number of factors, the cumulative impact of which intensifies the likelihood of injury.